Impact of service redesign on the socioeconomic inequity in revascularisation rates for patients with acute myocardial infarction: a natural experiment and electronic record-linked cohort study. Issue 10 (24th October 2016) - Evans, Lloyd W; van Woerden, Hugo; Davies, Gareth R; Fone, David
Abstract : Aim: To investigate the impact of service redesign in the provision of revascularisation procedures on the historical socioeconomic inequity in revascularisation rates for patients with acute myocardial infarction (AMI). Design: Natural experiment and retrospective cohort study using linked data sets in the Secure Anonymised Information Linkage databank. Non-randomised intervention: An increase in the capacity of revascularisation procedures and service redesign in the provision of revascularisation in late 2011 to early 2012. Setting: South Wales cardiac network, Census 2011 population 1 359 051 aged 35 years and over. Participants: 9128 participants admitted to an NHS hospital with a first AMI between 1 January 2010 and 30 June 2013, with 6-months follow-up. Main outcome measure: Hazard ratios (HRs) for the time to revascularisation for deprivation quintiles, age, gender, comorbidities, rural–urban classification and revascularisation facilities of admitting hospital. Results: In the preintervention period, there was a statistically significant decreased adjusted risk of revascularisation for participants in the most deprived quintile compared to the least deprived quintile (HR 0.80; 95% CI 0.69 to 0.92, p=0.002). In the postintervention period, the increase in revascularisation rates was statistically significant in all quintiles, and there was no longer any statistically significant difference in the adjusted revascularisation risk between the most and the least deprived quintile (HR 1.04; 95% CI 0.89 to 1.20, p<0.649). However, inequity persisted for those aged 75 years and over (HR 0.40; 95% CI 0.35 to 0.46, p<0.001) and women (HR 0.77; 95% CI 0.70 to 0.86, p<0.001). Conclusions: Socioeconomic inequity of access to revascularisation was no longer apparent following redesign of revascularisation services in the south Wales cardiac network, although inequity persisted for women and those aged 75+ years. Increasing the capacity of revascularisation did not differentially benefit participants from the least deprived areas.